2015
DOI: 10.1309/ajcp4plff1ttkent
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Changes in a Patient With Anorexia Nervosa

Abstract: The gross findings in the heart correlate with the previously described anomalies on cardiac ultrasound of patients with AN. The fibrosis and myxoid material deposition might be a direct consequence of starvation and the mechanism of death in some patients with AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…This study corroborates older data suggesting regional myocardial contraction abnormalities in patients in the acute phase of eating disorders . Although echocardiographic atrophy and fibrosis by MRI have been demonstrated, cardiac histologic abnormalities have been poorly characterized until very recently: a published autopsy report showed left ventricular atrophy with endocardial and interstitial fibrosis, focal myxoid material deposition with mast cells, and increased cytoplasmic lipofuscin . These findings may suggest the presence of an important risk of sudden cardiac death that is independent of delayed repolarization.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…This study corroborates older data suggesting regional myocardial contraction abnormalities in patients in the acute phase of eating disorders . Although echocardiographic atrophy and fibrosis by MRI have been demonstrated, cardiac histologic abnormalities have been poorly characterized until very recently: a published autopsy report showed left ventricular atrophy with endocardial and interstitial fibrosis, focal myxoid material deposition with mast cells, and increased cytoplasmic lipofuscin . These findings may suggest the presence of an important risk of sudden cardiac death that is independent of delayed repolarization.…”
Section: Methodssupporting
confidence: 89%
“…19 Although echocardiographic atrophy and fibrosis by MRI have been demonstrated, cardiac histologic abnormalities have been poorly characterized until very recently: a published autopsy report showed left ventricular atrophy with endocardial and interstitial fibrosis, focal myxoid material deposition with mast cells, and increased cytoplasmic lipofuscin. 32 These findings may suggest the presence of an important risk of sudden cardiac death that is independent of delayed repolarization. Although most cardiac structural abnormalities are reversible in this condition, the presence of myocardial scar suggests that malignant arrhythmias due to underlying structural heart disease remain a possible mechanism of increased mortality in this disease.…”
Section: Structural Complicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…1 Importantly, AN carries one of the highest mortality rates of any psychiatric illness, with a six-fold higher estimated death rate compared with age-matched peers. 5 In addition, patients with AN have been shown to have myocardial fibrosis, demonstrated by late gadolinium enhancement on cardiac magnetic resonance imaging, 6 endomyocardial biopsy, 7 and autopsy reports, 8 implicating a primary substrate for ventricular tachyarrhythmias. While AN is known to alter cardiovascular structure and function, and possibly cardiac repolarization, whether these abnormalities represent a mechanistic link to the high risk of sudden death in AN remains uncertain, primarily because definitive data on the occurrence of premorbid cardiac arrhythmias are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated myocardial fibrosis/scar manifested by late gadolinium enhancement on magnetic resonance imaging (MRI) in nearly a quarter of patients 61. Although echocardiographic atrophy and fibrosis by MRI have been demonstrated, histologic abnormalities in the heart have been poorly characterized until very recently: a published autopsy report showed left ventricular atrophy with endocardial and interstitial fibrosis, focal myxoid material deposition with mast cells, and increased cytoplasmic lipofuscin 62. Although most cardiac structural…”
mentioning
confidence: 99%